Sleep and antidepressant treatment - Wichniak, Adam; Wierzbicka, Aleksandra; Jernajczyk, Wojciech (Current pharmaceutical design, 2012)
The aim of this review was to describe the sleep anomalies in depression, the effects of antidepressants on sleep, the usefulness of antidepressants in the treatment of primary insomnia and insomnia in other psychiatric disorders. Depression is associated with abnormalities in the sleep pattern that include disturbances of sleep continuity, diminished slow-wave sleep (SWS) and altered rapid eye movement (REM) sleep parameters. Although none of the reported changes in sleep are specific to depression, many of them, for example increased REM density and reduced amount of SWS in the first sleep cycle, are used as biological markers for research on depression and in the development of antidepressant drugs. An antidepressant should reverse abnormalities in the sleep pattern. However, many antidepressants can worsen sleep. Because of the activating effects of some drugs, for example imipramine, desipramine, fluoxetine, paroxetine, venlafaxine, reboxetine and bupropion, many patients who take them have to be co-prescribed with sleep-promoting agents to improve sleep. Even in maintenance treatment with activating antidepressants as many as 30-40% of patients may still suffer from insomnia. Antidepressants with sleep-promoting effects include sedative antidepressants, for example doxepin, mirtazapine, trazodone, trimipramine, and agomelatine which promotes sleep not through a sedative action but through resynchronization of the circadian rhythm. Sedative antidepressants are frequently used in the treatment of primary insomnia, although not many double-blind studies have been provided to support such an approach to insomnia treatment. One exception is doxepin, which has been approved for the treatment of insomnia characterized by difficulties in maintaining sleep.